Studies on gonadosomatic index, fecundity and hatchability of domesticated stock of asala Schizothorax richardsonii (Gray) from Nallu River of Lalitpur District - Wagle, Suresh Kumar (Our Nature, 2015)
The present work embodies studies on the reproductive capacity of captive stock of asala Schizothorax richardsonii collected from Nallu River of Lalitpur district. Gonadosomatic index (GSI) estimates ranged from 3.08±0.9% in May to 26.55±1.8% in November. Positive correlation (r=0.667) was found between egg size and GSI. The egg size (2.7 to 2.9 mm) in October and November was significantly (P<0.01) larger than the eggs measured in other months. Based on peak GSI level, S. richardsonii spawned by manual stripping in two breeding season i.e. winter (October-November) and summer (Mach-April) in Godawari (1500 masl). Mean incubation period of fertilized eggs was 259 h and 248 h during winter and summer season at 14.2 to17.5 oC and 14.5 to15.5 oC water temperature, respectively. Percent hatching rates of eggs ranged between 38 to 90% and were not significantly different (P>0.05) between breeding seasons. Overripe eggs obtained during winter season breeding (16.5%) were significantly higher (P<0.01) than the summer season breeding (3.6%). This suggests that more frequent observation of the spawner is necessary during winter season for recognizing their appropriateness to ovulation. DOI: http://dx.doi.org/10.3126/on.v12i1.12253 Our Nature (2014), 12(1): 19-27